Evidence of Inbreeding in Hodgkin Lymphoma. - Hauke Thomsen; Miguel Inacio da Silva Filho; Michael Fuchs; Sabine Ponader; Elke Pogge von Strandmann; Lewin Eisele; Stefan Herms; Per Hoffmann; Andreas Engert; Kari Hemminki; Asta Försti (PLoS ONE, 2016)
Genome-wide association studies (GWASs) have identified several, mainly co-dominantly acting, single-nucleotide polymorphisms (SNPs) associated with Hodgkin lymphoma (HL). We searched for recessively acting disease loci by performing an analysis of runs of homozygosity (ROH) based on windows of homozygous SNP-blocks and by calculating genomic inbreeding coefficients on a SNP-wise basis. We used data from a previous GWAS with 906 cases and 1217 controls from a population with a long history of no matings between relatives. Ten recurrent ROHs were identified among 25 055 ROHs across all individuals but their association with HL was not genome-wide significant. All recurrent ROHs showed significant evidence for natural selection. As a novel finding genomic inbreeding among cases was significantly higher than among controls (P = 2.11*10-14) even after correcting for covariates. Higher inbreeding among the cases was mainly based on a group of individuals with a higher average length of ROHs per person. This result suggests a correlation of higher levels of inbreeding with higher cancer incidence and might reflect the existence of recessive alleles causing HL. Genomic inbreeding may result in a higher expression of deleterious recessive genes within a population.